Estudo das alterações neuropatológicas e do comportamento em tarefas hipocampo-dependentes induzidas pela encefalite experimental aguda associada ao vírus piry - REIS, Renata Rodrigues dos (2012)
This study investigated neuropathological changes and behavior in hippocampaldependent tasks induced by encephalitis caused by Piry arbovirus. Three temporal windows (3, 7 and 10 days post infection) and two environmental conditions were assessed to measure possible effects of the environmental enrichment on infection- induced changes. Two months old female mice, maintained in impoverished (IE) or in enriched environment (EE) by six months were tested in burrowing, open field and olfactory discrimination. After this period, all animals were intranasally inoculated with 5 μl of normal (NBH) or infected brain homogenate with Piry arbovirus (PY) and then reorganized into the following groups with seven animals each: IENBH, IEPY, EENBH and EEPY. After three, seven and ten days post instillation (dpi), they were perfused with aldehyde fixative. Their brains were removed, sectioned and the sections were processed either to imunohistochemical with anti-Piry or anti-Iba-1 to marker viral antigens and macrophage/microglial cells, respectively. Stereological quantifications were done in each CA3 layer using the optical fractionator method. Optical fractionator estimations revealed no changes in the number of microglial cells, indicating that this infection was not able to alter the number of cells, but microglia morphology, that revealed a higher number of pro-inflammatory morphological profiles in the IEPY than EEPY. Viral antigens were detected in the olfactory bulb, pyriform cortex, striatum and fimbria, following a sequence that mimics the anatomical olfactory pathway. In IEPY burrowing activity decreased in the first window and remained as such until the last window whereas in EEPY no changes were detected. Immobility increased in IEPY and remained altered until the last window; the number of crossing lines increased in the second and last windows; and the time on the center zone decreased in the second and last windows. In EEPY the immobility increased and correspondently the crossing lines reduced just in the second window. In olfactory discrimination, the main affected group was the IEPY, that didn‟t distinguish the two odors in the last window; in contrast EEPY group remained unaltered.